A novel role for C–C motif chemokine receptor 2 during infection with hypervirulent Mycobacterium tuberculosis. Issue 6 (November 2018) - Dunlap, Micah; Howard, Nicole; Das, Shibali; Scott, Ninecia; Ahmed, Mushtaq; Prince, Oliver; Rangel-Moreno, Javier; Rosa, Bruce; Martin, John; Kaushal, Deepak; Kaplan, Gilla; Mitreva, Makedonka; et al.
Abstract C–C motif chemokine receptor 2 (CCR2) is a major chemokine axis that recruits myeloid cells including monocytes and macrophages. Thus far, CCR2−/− mice have not been found to be susceptible to infection withMycobacterium tuberculosis (Mtb ). Here, using a prototype W-Beijing family lineage 2Mtb strain, HN878, we show that CCR2−/− mice exhibit increased susceptibility to tuberculosis (TB). Following exposure toMtb HN878, alveolar macrophages (AMs) are amongst the earliest cells infected. We show that AMs accumulate early in the airways following infection and express CCR2. During disease progression, CCR2-expressing AMs exit the airways and localize within the TB granulomas. RNA-sequencing of sorted airway and non-airway AMs from infected mice show distinct gene expression profiles, suggesting that upon exit from airways and localization within granulomas, AMs become classically activated. The absence of CCR2+ cells specifically at the time of AM egress from the airways resulted in enhanced susceptibility toMtb infection. Furthermore, infection with anMtb HN878 mutant lacking phenolic glycolipid (PGL) expression still resulted in increased susceptibility in CCR2−/− mice. Together, these data show a novel role for CCR2 in protective immunity against clinically relevantMtb infections.